2013
DOI: 10.1177/1071100713517102
|View full text |Cite
|
Sign up to set email alerts
|

Short-term Results of Total Ankle Arthroplasty for End-stage Ankle Arthritis With Severe Varus Deformity

Abstract: Level III, comparative series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…This possibly results in misalignment of the talus with respect to the anatomical axis of the tibia. Therefore, several surgeons have recommended resection of the lateral margin of the trochlea prior to placement of the cutting guide, to take the medial surface resorption into account 23,24 . The present results would help determine how the resection of the lateral margin of the trochlea should be made prior to placement of the cutting guide, possibly resulting in better clinical outcomes of total foot arthroplasty.…”
Section: Discussionmentioning
confidence: 99%
“…This possibly results in misalignment of the talus with respect to the anatomical axis of the tibia. Therefore, several surgeons have recommended resection of the lateral margin of the trochlea prior to placement of the cutting guide, to take the medial surface resorption into account 23,24 . The present results would help determine how the resection of the lateral margin of the trochlea should be made prior to placement of the cutting guide, possibly resulting in better clinical outcomes of total foot arthroplasty.…”
Section: Discussionmentioning
confidence: 99%
“…14 Two studies did not report the diagnoses, 27,38 and 1 study reported the diagnoses in number of patients instead of TARs. 32 The weighted mean BMI in the studies was 26.9 (range, 22-39) kg/m 2 and was reported in only 7 studies. The weighted mean follow-up using all included studies was 52.4 (range, 1-147) months: in the neutral alignment group, which was reported in 13 studies, weighted mean follow-up was 55.7 (range, 1-147) months.…”
Section: Resultsmentioning
confidence: 93%
“…The items “outcome of interest” and “comparability of cohorts” corresponded with the highest risk of bias across studies. Seven studies scored no stars for the item “outcome of interest,” 14,15,31,32,34,37,38 6 studies scored no stars for the item “comparability of cohorts,” 4,14,20,31,37,38 and 3 studies scored 1 of 2 stars for this item. 13,15,34 For the other items of the checklist, where a maximum of 1 star could be obtained, 2 studies did not obtain a star.…”
Section: Resultsmentioning
confidence: 99%
“…The trend toward increased preoperative varus in the loosening group (−4.7 degrees vs −0.1 degrees for the no-loosening group) suggests that large varus deformities may be more resistant to correction with this type of TAA than valgus deformities. While numerous authors have recently shown no difference in revision rates with respect to preoperative coronal deformity, 11,22,30 newer generation implants involving minimal bone resection may be best reserved for cases with less deformity.…”
Section: Discussionmentioning
confidence: 99%